The influence of circuit training on the development of strength and speed-power abilities in basketball players of 18-19 years old - I.V. Strelnikowa; G. G. Polevoy (Physical Education of Students)
Purpose: to determine the influence of circuit training on the level of strength and speed-strength abilities development in basketball players of 18-19 years old at the pre-competitive and competitive stages of the training process. Material: athletes (n = 32) were divided into 2 groups of 16 people. The pedagogical experiment lasted 7 months. Tests were applied to determine speed-power abilities: standing long jump test (broad jump, cm); vertical jump test. Strength was evaluated by the following tests: pull-up bars; hanging leg raises (stall bars)). Results: it was determined that power and speed-power abilities are leading in basketball. It was proposed the set of physical exercises performed on the principle of circuit training. It was confirmed the expediency of the circuit training applying for the development of power and speed-power abilities in basketball players. It is established that the circular training in the preparatory and final parts of the training increases the speed and speed-strength indicators of basketball players. Conclusion: It is recommended the circuit training applying at the pre-competitive and competitive stages of the training process.